2022
DOI: 10.1038/s41398-022-02234-z
|View full text |Cite
|
Sign up to set email alerts
|

Are the antidepressant effects of insulin-sensitizing medications related to improvements in metabolic markers?

Abstract: Insulin-sensitizing medications were originally used in psychiatric practice to treat weight gain and other metabolic side effects that accompany the use of mood stabilizers, antipsychotics, and some antidepressants. However, in recent studies these medications have been shown to cause improvement in depressive symptoms, creating a potential new indication outside of metabolic regulation. However, it is still unclear whether the antidepressant properties of these medications are associated with improvements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Moreover, brain insulin resistance has been shown to alter dopamine turnover and induce anxiety- and depressive-like behaviors in mice 39 . Insulin-sensitizing medications have been used in psychiatric practice to treat weight gain and other metabolic side effects that accompany the use of some antidepressant SSRI drugs 40 . Interestingly, recent studies show that metformin and glitazones can cause improvement in mental health 40 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, brain insulin resistance has been shown to alter dopamine turnover and induce anxiety- and depressive-like behaviors in mice 39 . Insulin-sensitizing medications have been used in psychiatric practice to treat weight gain and other metabolic side effects that accompany the use of some antidepressant SSRI drugs 40 . Interestingly, recent studies show that metformin and glitazones can cause improvement in mental health 40 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated to inhibit the expression of TNF-α, IL-6, and IL-1β in monocytes. PPARG exerts negative regulation on the transcription of inflammation-responsive genes by antagonizing the activator protein-1 and NF-kB signaling pathways [35]. Therefore, the inflammatory response triggered by stress can potentially result in a compensatory reduction in PPARG levels within the body.…”
Section: Discussionmentioning
confidence: 99%
“…IR is a predictor of non-response to some antidepressants, it seems to be a state-marker of clinical or subclinical depression, moreover, some insulin-sensitizing interventions are beneficial for the treatment of major depressive disorder ( 18 ). Furthermore, a systematic review investigated the antidepressant effects of insulin-sensitizing medications and found that the use of insulin-sensitizing medications had a positive impact on depressive symptoms ( 19 ).…”
Section: Introductionmentioning
confidence: 99%